Análisis de mercado para la importación de taxis marca Chery de origen chino - Paredes Chiriboga, Julio Cesar (2014)
Imported vehicles can be a very profitable business in the local market, due to the low local production in Ecuador. It does not satisfy the national demand, which has an annual growth of 10% in the major cities. China is currently the largest producer of vehicles in the world, they have acomparative advantage with other countries, including Ecuador, as domestic production does not reach the levels of local, we must say that currently Chery branded vehicles are among the cheapest in the world market as its production is almost entirely automated, production costs are much lower than the competition and this one of the primary factors of the business, and the vehicle to be imported meet the highest standards in the market but one of the best sale prices . Also we have to keep in mind that with the implementation of resolution 66 of the COMEX in 2012, the importation of vehicles was limited to dealers, which was a very serious problem for this sector, forcing them to seek alternatives, including Plan Renova, which allows the import of vehicles without quotas, and without custom fees, provided they are held for sale taxi. The taxi market in Ecuador is not a market controlled by dealers and competition, taking note that urban taxis has no substitute product, but this market will be a very important one because of the restrictions placed by the government. From the ecological point of view, with the implementation of the plan Renova service of vehicles that have met their useful life in order to enter the market by issuing new units reduced gases since the old cars will be reduced and recycled. In this paper titling, after analysing economic, social and governmental factors, feasibility and profitability of importing taxis Fulwin brand Chery to Ecuador